O21 Chronic liver disease emergency admissions are for patients with preventable, established liver disease. (19th June 2022) - Sheiybani, Giovanna
Abstract : Introduction: Standardised mortality for patients (PTs) with chronic liver disease (CLD) has dramatically increased since 1970. There are well-described significant disparities in health and healthcare for PTs with CLD. We aimed to describe geographical variations in care and outcomes for PTs with CLD across the United Kingdom (UK). Methods: PTs admitted to hospital between 1/11/2019–30/11/2019 across the UK were included. Inclusion/exclusion criteria are defined in Figure 1 . Admission clinical, demographic and laboratory data were collected with outcome and trust-specific data. Sites were grouped by NHS region, hepatology centre level and outcome groups. Univariate and multivariate analyses (MVA) were performed. Results: 1179 admissions (1124 PTs) from 99 trusts were included. Median age was 58.00 (IQR 48.00–68.00); PTs were younger in the north of England. Whilst there was no significant regional variation in admissions per hospital, there was significant regional variation in level 2/3 centre admissions. ARLD was the predominant aetiology of CLD, followed by non-alcoholic fatty liver disease (NAFLD) (cumulative prevalence 87.62%); Scotland had the lowest proportion of admissions with ARLD. 84.99% of admissions were for PTs with pre-admission established CLD diagnoses, 67.01% had decompensated previously and 55.84% reported regular ongoing alcohol consumption. There was geographical variation in admissions for patients with established CLD diagnoses and previous decompensation. Admission mortality was 15.05%. Survivors and non-survivors were compared and MVA was utilised to determine independent variables significantly associated with mortality. This model included PT age, admission MELD score, admission for encephalopathy and critical care admission (AUC 0.78 (95% CI 0.74–0.82)). Admission to level 2/3 centres was not a significant variable impacting mortality when adjusted for variables within this model nor was use of an admission care bundle. When adjusted for model variables, only when analysing level 1 centres in isolation were there significant differences in mortality between NHS regions. Conclusions: There is geographical variation in admissions with CLD across the UK, including access to specialist hepatology centres. Healthcare resources need to be distributed to ensure equity of care. Nearly all admissions are for PTs with a pre-admission diagnosis of preventable liver disease. Screening, early detection and prevention of CLD need to be prioritised in the UK.